Online appointment system - Muhammad Zul Fahmi, Zaher (2018)
The title of Projek Sarjana Muda (PSM) is “Online Appointment System for Student and Lecturer” that will be developed to Faculty of Computer Science and Software Engineering (FSKKP). The main objective of the development of this system is to overcome the problems exist in the current manual system. The medium for this system is Internet so students can access the system wherever they are as long as there is Internet connection. This system will be developed as a web-based platform and will be created using server side scripting such as PHP with Apache Web Server, user side scripting such as HTML and MYSQL as a database for the system. The target users of this system are students and lecturers. Generally, this system explanation about background project, methodology that will be used, how the analysis executed, design of database and interface, implementation and testing of system. The online system become systematic and also regular missing data. Besides, extra features in the system such as security protection by using password is included.